2022
DOI: 10.2147/ijgm.s351831
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Glycolysis and Hypoxia Combined Gene Signature Predicts the Prognosis and Affects Immune Infiltration of Patients with Colon Cancer

Abstract: We aimed to characterize the expression patterns of glycolysis and hypoxia genes in colon cancers as well as their value in prognosis and immune microenvironment. Methods: The expression profiles were acquired from the Cancer Genome Atlas database. Enrichment of hypoxia and glycolysis gene sets in colon cancer was identified by gene set enrichment analysis. Then, a prognostic signature was built up after Cox regression analyses, and overall survival analysis validated the predictive ability. Immune status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Furthermore, ENO3 may have a unique function in promoting glycolysis in tumor cells. To date, several sequencing-based studies have reported that ENO3 is involved in glycolysis and colorectal or colon cancer and that elevated ENO3 promotes ATP production or glycolysis under hypoxic conditions [ 27 , 54 ]. Furthermore, genome analysis using the Gene Expression Omnibus database revealed that ENO3 is involved in glycolysis regulation; LASSO Cox analysis revealed that ENO is associated with prognosis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ENO3 may have a unique function in promoting glycolysis in tumor cells. To date, several sequencing-based studies have reported that ENO3 is involved in glycolysis and colorectal or colon cancer and that elevated ENO3 promotes ATP production or glycolysis under hypoxic conditions [ 27 , 54 ]. Furthermore, genome analysis using the Gene Expression Omnibus database revealed that ENO3 is involved in glycolysis regulation; LASSO Cox analysis revealed that ENO is associated with prognosis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enolase 3 (ENO3) is a β -enolase that regulates striated muscle development [ 26 ]. Genomic analysis revealed that ENO3 is associated with the risk of colon cancer and that it is involved in the regulation of glycolysis [ 27 ]. Elevated levels of glycolysis result in the activation of inflammatory pathways [ 28 ], which are also involved in tumor progression [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…STC2 is a glycoprotein hormone that promotes tumor development and invasion in several human malignancies. Mao et al showed that STC2 is a potential biomarker for tumor behavior among colorectal cancer patients (44) and a GSEA analysis study reported that STC2 is linked to HNSCC cell growth (45). STC2 is also associated with lymph node metastasis in esophageal cancer patients (46).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org 13 Inhibition of CD36 might prove beneficial in repressing metastasis spread, which demonstrated clinical practice potential (Enciu et al, 2018). ENO3, as a glycolysis and hypoxia-related gene, could predict the prognosis and immune landscape of colon cancer patients (Cui et al, 2021;He et al, 2021;Mao et al, 2022). ENO3 could promote CRC cell proliferation and migration by promoting glycolysis metabolism (Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%